Examining Use of Dual Point Temperature Display in Servo-Control With Early Preterm Infants. (December 2021) - Dail, Robin B.; Tavakoli, Abbas S.; Moseley, Sherry L.; Bergstedt, Victoria B.; Kuehn, Devon; Chang, Weili
Abstract : Background: Previously, we recorded periods of time with foot higher than abdominal temperatures in association with infection in preterm infants. Monitoring dual temperatures may be an important tool to assess infant instability. Currently, incubators cannot measure and display dual temperatures in servo-control mode. Purpose: To examine the usability of GE Healthcare's Giraffe OmniBed with research software to measure, display, and record dual temperatures, and their differences while in servo-control. In addition, nurses' perceptions of the use and display of dual temperatures and differences were evaluated. Methods: A multiple-case, mixed-methods design. Abdominal and foot temperatures were measured, displayed, and stored for 28 days for 14 preterm infants. Nurses were surveyed for satisfaction and preferences with the dual temperature display. Nurses noted abnormal temperature differences and infant condition in bedside journals. Results: Study infants were 26 to 31 weeks of gestational age and 670 to 1410 g. Abdominal, foot, and the abdominal-foot temperature difference was measured, recorded, and downloaded successfully in all infants over all days. Nurses liked using dual temperature display with the abdominal-foot temperature difference. Surveys indicated preferences for larger displays and alarms for abnormal values. Thermal instability, stimulation, and thermistor detachment were associated with abnormal thermal gradients. Two exemplar cases are presented. Implications for Practice: Monitoring dual temperatures adds information to the clinical assessment. Implications for Research: Studies are needed to examine relationships between abnormal thermal gradients and infections, infant stability, and nursing care along with the underlying physiologic mechanisms. Studies are needed for wireless dual temperature monitoring. Abstract : Supplemental Digital Content is Available in the Text.